Implementation of the Values of the Qur'an Surah Luqman Verses 12-19 through the Character Strengthening Program of Students of the Hasyim Asy'ari Tarub Islamic Boarding School, Tegal Regency - Imron, Ali; Suriswo, Suriswo; Basukiyatno, Basukiyatno (Universitas Pahlawan Tuanku Tambusai, 2026)
This research is based on the development of the increasingly advanced era with increasingly sophisticated technology. The development of technology, the expansion of information media that has a positive and negative impact on children. The purpose of this research is to find out more about the values of Islamic education contained in the letter of Luqman verses 12 – 19, and the habituation of what is done in Islamic boarding schools related to the implementation of Islamic education values in the form of Aqidah educational values, Worship Values and Moral Values in their students. This research is a literature research using several interpretations as a reference to explore the values of Islamic education contained in Surah Lukman verses 12-19. The literature research is integrated with field research with a qualitative approach. This is to see the real implementation of Islamic educational values in the Hasyim Asy'ari Tarub Islamic boarding school. The results of the study show that the value of Islamic education is contained in Surah Lukman verses 12-19. Namely the educational value of Aqidah such as Lukman teaching his children not to do shirk, the value of worship such as Lukman telling his children to establish prayer and moral values such as Lukman telling his children to always do good and not to act arrogant.